IL‐11 and CCL‐1: Novel Protein Diagnostic Biomarkers of Lung Adenocarcinoma in Bronchoalveolar Lavage Fluid (BALF). Issue 12 (December 2016) - Pastor, Maria Delores; Nogal, Ana; Molina‐Pinelo, Sonia; Quintanal‐Villalonga, Álvaro; Meléndez, Ricardo; Ferrer, I.; Romero‐Romero, Beatrice; De Miguel, Maria José; López‐Campos, José Luis; Corral, Jesús; García‐Carboner, Rocío; Carnero, Amancio; et al.
ABSTRACT : Introduction: : Lung cancer (LC) and chronic obstructive pulmonary disease (COPD) are smoking‐related diseases, with the presence of COPD itself increasing the risk for development of LC, probably owing to underlying inflammation. LC is typically detected at late stages of the disease and carries a poor prognosis. There is an unmet need for methods to facilitate the early detection of LC in high‐risk subjects such as smokers. Methods: : The expression of inflammatory proteins in bronchoalveolar lavage fluid (BALF) samples was studied by antibody arrays in a prospective cohort of 60 smokers of more than 30 pack‐years divided into four groups (control, patients with LC, patients with COPD, and patients with LC plus COPD). Relevant biomarkers were validated by Western blot. Additional validation with enzyme‐linked immunosorbent assay (ELISA) was carried out on two independent controlled cohorts of 139 patients (control, patients with LC, patients with COPD, and patients with LC plus COPD) and 160 patients (control and patients with LC of all histological types). Results: : A total of 16 differentially expressed proteins in samples from patients with LC, COPD, and LC plus COPD were identified by antibody arrays and validated by Western blot and ELISA. C‐C motif chemokine ligand 1 (CCL‐1) and interleukin‐11 (IL)‐11 were selectively expressed in samples from patients with adenocarcinoma with or without COPD ( p < 0.005). These proteins exhibited a remarkable diagnostic performance for lung adenocarcinoma in an independent cohort of 139 patients. Receiver operating characteristic curves showed that the optimum diagnostic cutoff value for IL‐11 was 42 pg/mL (area under the curve = 0.93 [95% confidence interval: 0.896–0.975], sensitivity 90%, specificity 86%), whereas for CCL‐1 it was 39.5 pg/mL (0.83 [95% confidence interval: 0.749–0.902], sensitivity 83%, and specificity 74%). Further validation of the ELISA biomarkers at the aforementioned cutoffs was performed in an additional cohort of 160 patients (20 controls, 66 patients with LC, and 74 patients with LC plus COPD). There was a significant correlation between BALF levels of IL‐11 and CCL‐1 ( r 2 = 0.76, p < 0.001), and the use of both biomarkers increased the diagnostic accuracy to 96.1% in the two validation cohorts. Appropriate diagnostic performance was observed for all subgroups regardless of stage at diagnosis, involvement of the bronchial tract, pack‐years smoked, and number of cells in BALF. Conclusions: : IL‐11 and CCL‐1 are highly specific biomarkers with great accuracy for the diagnosis of lung adenocarcinoma in BALF specimens. Further study of these proteins as markers for the early diagnosis and screening of plasma and other biological materials is warranted.